Penerapan Metode Servqual Dan Customer Satisfaction Index (CSI) Untuk Peningkatan Kepuasan Pengguna Light Rail Transit (LRT) Di Kota Palembang - Sahfitri, Vivi; Suyanto, suyanto; Dayi, Dayang (Jurnal Ilmiah Matrik, 2023)
One mode of mass transportation that is currently widely used by the people of Palembang City is Light Rail Transit (LRT). This research aims to determine the level of satisfaction of LRT mass transportation users in Palembang City using the ServQual method and the CSI method. Measuring the level of satisfaction uses 5 dimensions, namely Tangible, Reliability, Responsiveness, Assurance and Empathy. Measurements using the ServQual Method overall show that the level of satisfaction with the quality of service on the LRT in Palembang city is 0.908552, which is close to a value of 1, so it can be concluded that users are very satisfied with the quality of service on the LRT in Palembang city. However, based on the Gap obtained from Satisfaction and Expectations, each attribute in the 5 dimensions of service quality has a Negative Gap value which indicates that improvements still need to be made to increase user satisfaction in the future. Measuring the level of satisfaction using the CSI method obtained an LRT user satisfaction level index of 0.7659 in the range of 0.60 – 0.80, which means the satisfaction index for LRT mass transportation services is in the Satisfaction criteria